Hollow bulb one piece maxillary definitive obturator - A simplified approach - Sapna Rani; Sakshi Gupta; Mahesh Verma (Wolters Kluwer Medknow Publications, 2017)
In maxillary defects, role of a prosthodontist is to rehabilitate the intra- and extra-oral structures and to endow with the normal function of mastication, speech, deglutition, and esthetics. Malignancies are common in the oral region and are treated usually through surgical intervention. Surgical intervention creates anatomical defects creating communication between oral and nasal cavity. Patients pose difficulties while performing normal functions such as swallowing and speaking, due to this communication. To overcome the problems encountered by the patient, obturators are fabricated. The main problem with rehabilitation of large defect is the weight of prosthesis; the prosthesis becomes very bulky and nonretentive due to its weight. Hollow obturators are fabricated to conquer this tribulation by different techniques. This case report describes a simplified method of fabrication of a definitive hollow bulb obturator for rehabilitation of a maxillary defect (Aramany's class I) by insertion of balloon.